2018
DOI: 10.1002/wea.3305
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of the evolution of the boundary layer during a radiation fog event

Abstract: Despite the impact it has on human activity, particularly transport, accurate forecasting of fog remains a major challenge for numerical weather prediction models. The complex interaction between various physical processes, many of which are parametrised and highly sensitive to small changes, is one of the key reasons for poor fog forecasts. One challenge for numerical models is predicting the structure of the boundary layer, which often undergoes a transition from statically stable to weakly unstable during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
(28 reference statements)
0
16
1
Order By: Relevance
“…Recent studies of IOP 1 have shown that humidity and wind speed in the residual layer control the optical thickening of the fog (Smith et al, 2018), in addition to the hygroscopic growth and the fraction of CCN activated into droplets (Boutle et al, 2018). Over the same case, Poku et al (2019) recently showed, with a two-moment microphysical scheme using a single mode of CCN, that the CCN number concentration has a greater impact on fog water content than the CCN soluble fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of IOP 1 have shown that humidity and wind speed in the residual layer control the optical thickening of the fog (Smith et al, 2018), in addition to the hygroscopic growth and the fraction of CCN activated into droplets (Boutle et al, 2018). Over the same case, Poku et al (2019) recently showed, with a two-moment microphysical scheme using a single mode of CCN, that the CCN number concentration has a greater impact on fog water content than the CCN soluble fraction.…”
Section: Discussionmentioning
confidence: 99%
“…At Cardington, fog formed around 1800 utc and remained stable, as well as optically thin, through the duration of the night. IOP1 was chosen as it was one of the cleanest examples of local fog development, with minimal influence by advective processes (see Smith et al , for more details).…”
Section: Model Setupmentioning
confidence: 99%
“…Deep adiabatic radiation fogs are typically longer‐lived, with a greater potential to persist during the day and thus a greater impact (Price, 2011). The stability transition is sensitive to various conditions, including aerosol concentrations (Boutle et al ., 2018; Poku et al ., 2019), wind speed, and humidity (Smith et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%